Contribution to the taxonomy and ecology of Strandesia s.l. (Crustacea, Ostracoda, Cypricercinae) from Brazilian floodplains. - Ferreira, Vitor Góis (2019)
The pourpose of this revision of Strandesia s.l. species in Brazil was to validate the taxonomic position of your representants. Among eleven genera, Strandesia is the most diverse one in the Cypricercinae, with seventeen species recorded from Brazil. This study reports on Strandesia species of four major Brazilian floodplains: Amazon, Araguaia, Pantanal and Paraná. Three new species of Strandesia are described, together with the first record and description of a male population of another species, S. obtusata, from Brazil. As a result of the revision, one new Cypricercinae genus and a new species are described. The new genus and species represent a case of convergent evolution with Bradleytriebella lineata (Victor and Fernando, 1981), owing to the similarities in carapace shape and ornamentation, but clear differences in soft parts characters.